Penerapan Oven Pengasapan Dalam Pengolahan Telur Asin Asap Pada Warga UKM Kampung Sialang Baru - Yusfiati, Yusfiati; Surianto, Muhammad Akbar; Hidayatullah, Abda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Sialang Baru Village since the Covid 19 pandemic has affected the local community's economy, especially in the business of processing duck eggs into salted eggs. So far, the use of duck eggs that have not been optimal has become an obstacle in developing their business. The purpose of this service is to find a way to make smoked salted eggs using an efficient and inexpensive oven. The result of making smoked salted eggs using a smoking oven from an oil drum-sized drum produces smoked salted eggs that have a gritty egg yolk texture and taste better than unsmoked salted eggs. The color of salted eggs is better which is light brown compared to using smoking eggs with a gas smoking oven. The cost of making an oven is cheaper than making a gas smoking oven. The smoking oven has helped the UKM community of Kampung Silang Baru in producing smoked salted eggs that are efficient, so that it is possible to further improve the UKM economy.